Evaluation of guava (Psidium guajava) and bael (Aegle marmelos) under shallow saline watertable conditions - SINGH, ANSHUMAN; KUMAR, ASHWANI; DATTA, ASHIM; YADAV, R K (The Indian Journal of Agricultural Sciences, 2018)
Growth, physiological activities and leaf ionic relations were studied in guava (Psidium guajava L.) cv. Allahabad Safeda and bael (Aegle marmelos Correa) cv. NB-5 planted under shallow saline watertable conditions. Marginally saline (MSW; ECIW 4 dS/m) and saline (SW; 6 dS/m) waters were applied either in cyclic (C) mode with the best available water (BAW; 2.8 dS/m) or regularly (R) to impose five salinity levels: control (BAW), CMSW (MSW and BAW in cyclic mode), RMSW (regular application of MSW), CSW (SW and BAW in cyclic mode) and RSW (regular application of SW). Data were recorded 120 days after salt treatment (DAST). In CSW and RSW treatments, salt injury symptoms (leaf yellowing, marginal scorch and chlorosis) appeared around 60 DAST in both the crops. Although plant height and stem girth were relatively less affected, branch and leaf emergence considerably decreased with increase in salinity giving the salinized plants a sparse look. Regular irrigation with 6 dS/m water caused substantial reductions in net photosynthesis (37-45%), photochemical efficiency (Fv/Fm ratio; 11-21%) and total soluble sugars (≈30%); and increase in proline, Na+ and Cl- levels in leaves. Leaf proline was nearly fivefold higher in guava and threefold higher in bael at 6 dS/m salinity than BAW irrigated plants. Both the crops exhibited ≈8 fold higher leaf Na+/K+ ratio and considerable increase in leaf Cl- when continuously irrigated with 6 dS/m water. Plant growth, physiological attributes and leaf ionic composition in CMSW treatment were comparable to BAW treated plants indicating that marginally saline water (ECIW ≈ 3-4 dS/m) can be used to irrigate guava cv. Allahabad Safeda and bael cv. NB-5 planted in saline soils.